Komunikasi Arduino I2C, SPI dan UART - Sigit Prakosa Adhi Nugraha; Lilo Sunuharjo; Muhammad 'Atiq (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
Communication between devices is an important aspect when developing an Arduino-based system. The three communication protocols commonly used with Arduino are I2C (Inter-Integrated Circuit), SPI (Serial Peripheral Interface), and UART (Universal Asynchronous Receiver/Transmitter). Each of these protocols has unique characteristics that make them suitable for different applications. These three communication protocols provide flexible options when developing systems that communicate with sensors, actuators, or other modules on the Arduino platform. Selecting the appropriate protocol depends on specific needs, such as speed, number of connected devices, and system complexity.